Willingness to adopt biodegradable mulch among farmers in Saudi Arabia: implications for agricultural extension - Muddassir, Muhammad; Alotaibi, Bader Alhafi; Azeem, Muhammad Imran (Frontiers in Sustainable Food Systems, 2024)
Biodegradable mulch (BDMs) films are ecologically safe substitutes for polyethylene mulches (PEMs) in agricultural systems. However, since it is an innovative technology on the market, it is not easy for farmers to adopt it. Understanding farmers' familiarity with BDM and their willingness to adopt it in the future could play a crucial role in the design and implementation of effective agricultural interventions for promoting the adoption of BDM to reduce environmental pollution. Therefore, a study was undertaken to assess farmers' familiarity with BDM and their willingness to adopt it in the future. Data were collected from fruit and vegetable growers located in Al-Kharj, Saudi Arabia, using a simple random sampling approach with the help of a pre-tested paper-based questionnaire. The findings revealed that most of the farmers were not familiar with BDM. Despite the lack of awareness, a considerable portion indicated their willingness to adopt BDM in the future. The farmers' education level, farm size, and membership in agricultural cooperatives significantly influenced their familiarity with BDM. Education level, farming experience, and membership in agricultural cooperatives also showed significant relationships with their willingness to adopt BDM in the future. Moreover, the farmers were not aware of the potential benefits of this new innovation. The study recommends that extension education programs through the active involvement of agricultural cooperatives should be implemented to make farmers aware of the advantages of BDM over PEM. In addition, the government should facilitate the adoption of this promising innovation by enhancing its availability on the market and affordability to farmers.